1999
DOI: 10.1046/j.1442-1984.1999.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of Trilliaceae II. Phylogenetic analyses of Trillium and its allies using sequences of rbcL and matK genes of cpDNA and internal transcribed spacers of 18S–26S nrDNA

Abstract: Coding regions of the rbcL and matK genes of cpDNA and internal transcribed spacers (ITS) of nuclear ribosomal DNA were sequenced to study phylogenetic relationships within and among all four genera of Trilliaceae: Trillium, Paris, Daiswa and Kinugasa. The rbcL gene has evolved much slower than matK and in particular ITS; hence the phylogenetic trees based on the rbcL gene show a much lower resolution than trees based on either matK or ITS. The general topology of phylogenetic trees resulting from separate par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 67 publications
1
21
1
Order By: Relevance
“…Our phylogenomic analyses also well resolved the inter-tribe relationships in the family Melanthiaceae and the inter-generic relationships within the tribe Parideae, with higher support than previous phylogenetic studies that used single or multiple locus DNA sequences data (Osaloo and Kawano, 1999; Farmer and Schilling, 2002; Ji et al, 2006; Kim et al, 2013). This result was consistent with previous findings (Attigala et al, 2016) in which a much higher of support to inter-generic relationships was observed in the cp genomic phylogeny within Arundinarieae tribe (Bambusoideae: Poaceae).…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Our phylogenomic analyses also well resolved the inter-tribe relationships in the family Melanthiaceae and the inter-generic relationships within the tribe Parideae, with higher support than previous phylogenetic studies that used single or multiple locus DNA sequences data (Osaloo and Kawano, 1999; Farmer and Schilling, 2002; Ji et al, 2006; Kim et al, 2013). This result was consistent with previous findings (Attigala et al, 2016) in which a much higher of support to inter-generic relationships was observed in the cp genomic phylogeny within Arundinarieae tribe (Bambusoideae: Poaceae).…”
Section: Discussionsupporting
confidence: 64%
“…Compared to previous molecular phylogeneitc analyses (Osaloo and Kawano, 1999; Ji et al, 2006; Farmer and Schilling, 2002), our results clearly indicated that all nodes within the Daiswa clade showing a MLBS > 90% and PP > 0.95 ( Figure 3 ). Similar results have also been observed from the whole chloroplast genome analysis of Pinus species (Parks et al, 2009), Araucaria species (Ruhsam et al, 2015), and Acasia species (Williams et al, 2016).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations